Filsafat Ilmu Pendidikan Agama Kristen Dan Praksisnya Bagi Agama Kristen Di Masa Kini - Erika Yusthina Balol; Marnike Jayati Zega (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
Philosophy is a method of thinking systematically and critically. In connection with Christian religious education, it must be studied systematically and critically as basis for knowledge so that it is parallel to other sciences that show real benefits for the development of humanity. The author will describe Christian Religious Education as a science praxis ontologically, epistemologically and axiologically. The method used in this research is systematic literature study approach. Ontologically Christian religious education must be a strong guide towards the journey of human life so that it is able to exist and exist both theologically and socially. Epistemology talks about knowledge. Epistemologically, the Bible and Jesus are the epistemological sources of Christian religious education. Axiology speaks of utility value. The axiological foundation of Christian Religious Education is a loving humanist inspired by Christian values. In other words, it axiology helps to humanize humans and free them from the alienation of their human role in life.